Social media addiction and depression among adolescents in two Malaysian states - Stephanie Ann Victor; Muhamad Shamsul Ibrahim; Sarina Yusuf; Norasyikin Mahmud; Khairul Azam Bahari; Loh Yoke Ling; Nur Nadia Abd Mubin (International Journal of Adolescence and Youth)
Addiction to social media addiction is considered a leading risk factor for depression among adolescents, but the relationship needs to be supported empirically. This study investigates the social media addiction level and its association with depression among Malaysian adolescents. A cross-sectional study was conducted by distributing a structured questionnaire to potential respondents aged 13 to 21 years old from Johor and Sarawak. Data were analysed in SPSS using descriptive statistics, correlation, and Chi-square tests. Overall, 72.0% and 33.0% of the 384 respondents recorded high levels of social media addiction and depression, respectively. A significant and low positive relationship was detected between social media addiction and depression among adolescents. The levels of social media addiction and depression differed across age groups, gender, race, and the time spent on social media platforms. These findings reflect the need to address excessive social media usage among adolescents.